ELT and Citizenship: Basic Principles to Raise Social Awareness Through Language Teaching - Javier Rojas Serrano (Asociación Colombiana de Profesores de Ingles, 2008)
In this paper, I delve into the concept of citizenship in connection with the teaching of English as an auxiliary channel for increasing social awareness and understanding among teachers and students. Taking into consideration current global realities and the local contexts in which English is acquired and used, I feel that foreign language classrooms become an important space in which students can identify with the social structures of different cultures as well as the roles they play in their own society. Thus, I will address basic concepts and principles for developing citizenship awareness and ELT instruction from perspectives as diverse as educational background, curriculum development, methodologies and student and teacher roles, among others.